PENGARUH SENAM PROLANIS TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI: LITERATURE REVIEW - Isna Sulistiawati Ningrum; Lilis Lismayanti (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Hypertension is a major health problem that continues to show an increasing trend in Indonesia and requires continuous treatment. One of the common efforts carried out in primary health facilities is Prolanis exercise, which is a regular physical activity intended for patients with chronic diseases. This study was conducted to determine the extent to which Prolanis exercise contributes to lowering blood pressure in hypertensive patients. Literature review was conducted using Google Scholar, Garuda, and PubMed for publications from 2019 to 2024 using a combination of keywords related to hypertension and Prolanis exercise. All articles obtained were examined for eligibility through a selection process based on inclusion and exclusion criteria, then analyzed through data matrix compilation. Four articles met the criteria and generally showed that regular Prolanis exercise exercise program can reduce both systolic and diastolic blood pressure. The magnitude of the reduction was influenced by exercise frequency, program duration, and participant conditions. Overall, Prolanis exercise can be used as an effective intervention in controlling hypertension in primary health care facilities